Mengoptimalkan Platform Pembelajaran Online untuk Meningkatkan Keterlibatan Siswa Selama Pandemi COVID-19 - Darlan, Muhamad; Sekti, Binastya Anggara; Hasanah, Diannur (Ikatan Ahli Informatika Indonesia, 2024)
The COVID-19 pandemic has necessitated drastic changes in higher education, leading to a sudden shift to online learning. This literature review analyzes the effectiveness, influencing factors, challenges, and solutions in the context of online learning during the pandemic from 2020 to 2022. A systematic review methodology was employed, including searches in major databases, screening of 150 initial articles, and final analysis of 50 selected studies. The results show a positive effectiveness of online learning (d = 0.38), emphasizing the quality of teacher-student interaction, course design, technology competency, institutional support, and intrinsic motivation. Challenges like internet connectivity and social interaction were identified, with solutions including technology infrastructure, digital training, alternative assessment methods, and psychosocial support. Further research is recommended for longitudinal studies and specific strategies to enhance student engagement in online learning.